Recurrent Orbital Subperiosteal Abscess in Patient with Nasopharyngeal Carcinoma: Poster Presentation - Case Report - Resident - Mefina Aulia Mufidah; Lukman Edwar; Mutmainah; Rwtno Sulistyo Wardani (Majalah Oftalmologi Indonesia, 2023)
Introduction : Subperiosteal abscess (SPA) is a rare finding in cancer patients with orbital cellulitis. Severe complications associated with this condition are permanent visual loss, intracranial extension, and death. Case Illustration : A 38-year-old male with history of nasopharyngeal carcinoma (NPC) came with progressive right eyelid swelling, non-axial proptosis, and visual acuity was NLP. CT scan revealed right SPA associated with frontal sinusitis. NPC staging was T3N2M0. Despite the treatment of intravenous antibiotics and drainage incision of SPA, there was recurrence of right SPA two weeks after procedure and re-staging revealed T4N3M0. A joint operation with otolaryngology department to do debulking of the mass, frontal sinus surgery, and drainage incision was held. Culture resulted in Talaromyces marneffei. Patient was assessed with talaromycosis and given itraconazole for ten weeks. Moreover, patient came again with proptosis seven weeks postoperatively. Re-drainage incision was performed and clinical presentation was improved. Discussion : This case describes rare biological nature of NPC where extensive blockage of paranasal sinuses allows microorganism overgrowth and infection. The anatomical changes and cancer-related immunosuppression contribute to recurrent SPA. Chemotherapy and radiotherapy are ideal treatments for our patient, however, infection must be treated adequately first. Surgical interventionis needed to manage the infection by SPA drainage where antimicrobial has poor penetration into the abscess and debulking of tumor to clear the blockage of drainage pathway. Conclusion : Recurrent orbital SPA could happen in patients with NPC, therefore appropriate medical treatment and timely surgical intervention are essential in managing orbital SPA. Multidisciplinary management is required to optimize patient outcomes.